THE PRIORITY NEEDS FOR STUDENT AFFAIRS MANAGEMENT OF VAJIRAVUDH COLLEGE BASED ON THE CONCEPT OF VALUABLE LIFE - Samarnmoo, Preechaphol; Petpon, Ponglikit (Journal of Educational Review Faculty of Education in MCU, 2024)
The purpose of this research is to study the priority needs in the student affairs management development of Vajiravudh College, according to the concept of Valueable life. A descriptive research method is used in this research. The tools used in the research were questionnaires. The data were analyzed by arithmetic mean, standard deviation, and the modified Priority Needs Index (PNIModified). The survey was completed by 85 people, who were all administrators and secondary school teachers at Vajiravudh College. The finding showed that 1) Current conditions were at a moderate level, with the extra-curricular activities having the highest mean and the student discipline and supervision having the lowest mean. The desired condition was at a high level, with teaching and learning management having the highest mean and discipline and supervision with the lowest mean. 2) With the Priority Need Index, the academic concept was 0.537 overall (PNIModified = 0.537). In consideration of the scope of student affairs management, it was discipline and supervision with the highest order of needs, followed by the extra-curricular activities with the lowest order of needs. Considering the attributes of a Valuable life, it was found that encouraging students to be ready to cope with change had the highest of development needs, and promoting students' ability to learn had the lowest of development needs.